Earthworks : a guide - Nowak, Paul; Gilbert, Peter; Trenter, N. A. (ICE Publishing, 2015)
Although normally seen as major structures, such as earth fill dams or large highways or railway embankments, the majority of earthworks are connected with minor civil works and building construction. Whatever the type of work, the principles are the same. This title accumulates information on topics that are essential to earthworks engineering.
Keywords: Earthwork -- Handbooks, manuals, etc.; Civil engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books